Neutrophil‐to‐lymphocyte ratio and platelet‐to‐lymphocyte ratio as predictors of survival after heart transplantation. (31st July 2017) - Seropian, Ignacio M.; Romeo, Francisco J.; Pizarro, Rodolfo; Vulcano, Norberto O.; Posatini, Ricardo A.; Marenchino, Ricardo G.; Berrocal, Daniel H.; Belziti, Cesar A.
Abstract: Aims: The aim of this study was to evaluate whether neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) predict outcome in heart failure (HF) patients undergoing heart transplantation (HTX). Methods and results: Data from 111 HF patients undergoing HTX 2010–2015 were retrospectively reviewed. NLR and PLR were calculated before HTX, immediately after HTX, and at 6 and 24 hours. Primary endpoint was in‐hospital mortality, and secondary endpoints were 1 year mortality and renal replacement therapy (RRT). Prognostic factors were assessed by multivariate analysis, and the predictive values of NLR and PLR for mortality were compared. The discriminatory performance for predicting in‐hospital mortality was better for NLR [area under the receiver operating characteristic curve (AUC) = 0.644, 95% confidence interval 0.492–0.797] than for PLR (AUC = 0.599, 95% confidence interval 0.423–0.776). Best cut‐off value was 2.41 for NLR (sensitivity 86%, specificity 67%) and 92.5 for PLR (sensitivity 86%, specificity 68%). When divided according to best cut‐off value, in‐hospital mortality was significantly higher in the high NLR group (17.5% vs. 3.2%, P  < 0.05), but not in the high PLR group (16.5% vs. 6.3%, P  = ns). One year mortality was not significantly higher for either group (37.5% vs. 6.5% for NLR; 36.7% vs. 9.4% for PLR, P  = ns for both), while RRT was significantly higher in both the NLR and PLR high groups (33.8% vs. 0%; 32.9% vs. 3.1%, respectively, P  < 0.001). Multivariate analysis indicated that only high NLR (hazard ratio = 3.403, P  < 0.05) and pre‐transplant diabetes (hazard ratio = 3.364, P  < 0.05) were independent prognostic factors for 1 year mortality. Conclusions: High NLR was a predictor for in‐hospital mortality, and an independent prognostic factor for 1 year mortality. Both high NLR and high PLR were predictors for RRT.